Hippocampal Neurochemical Profile and Glucose Transport Kinetics in Patients With Type 1 Diabetes - Bednařík, Petr; Henry, Pierre-Gilles; Khowaja, Amir; Rubin, Nathan; Kumar, Anjali; Deelchand, Dinesh; Eberly, Lynn E; Seaquist, Elizabeth; Öz, Gülin; Moheet, Amir (The Journal of clinical endocrinology and metabolism, 2020)
CONTEXT: Longstanding type 1 diabetes (T1D) may lead to alterations in hippocampal neurochemical profile. Upregulation of hippocampal glucose transport as a result of recurrent exposure to hypoglycemia may preserve cognitive function during future hypoglycemia in subjects with T1D and impaired awareness of hypoglycemia (IAH). The effect of T1D on hippocampal neurochemical profile and glucose transport is unknown. OBJECTIVE: To test the hypothesis that hippocampal neurochemical composition is altered in T1D and glucose transport is upregulated in T1D with IAH. DESIGN AND PARTICIPANTS: Hippocampal neurochemical profile was measured with single-voxel magnetic resonance spectroscopy at 3T during euglycemia in 18 healthy controls (HC), 10 T1D with IAH, and 12 T1D with normal awareness to hypoglycemia (NAH). Additionally, 12 HC, 8 T1D-IAH, and 6 T1D-NAH were scanned during hyperglycemia to assess hippocampal glucose transport with metabolic modeling. SETTING: University medical center. MAIN OUTCOME MEASURES: Concentrations of hippocampal neurochemicals measured during euglycemia and ratios of maximal transport rate to cerebral metabolic rate of glucose (Tmax/CMRGlc), derived from magnetic resonance spectroscopy-measured hippocampal glucose as a function of plasma glucose. RESULTS: Comparison of hippocampal neurochemical profile revealed no group differences (HC, T1D, T1D-IAH, and T1D-NAH). The ratio Tmax/CMRGlc was not significantly different between the groups, T1D-IAH (1.58 ± 0.09) and HC (1.65 ± 0.07, P = 0.54), between T1D-NAH (1.50 ± 0.09) and HC (P = 0.19), and between T1D-IAH and T1D-NAH (P = 0.53). CONCLUSIONS: Subjects with T1D with sufficient exposure to recurrent hypoglycemia to create IAH did not have alteration of Tmax/CMRglc or neurochemical profile compared with participants with T1D-NAH or HC.
Keywords: upregulace; Glucose Clamp Technique; glykemický clamp; Humans; Up-Regulation; lidé středního věku; Female; dospělí; Hippocampus; lidé; magnetická rezonanční spektroskopie; hipokampus; glukosa; hyperglykemie; hypoglykemie; Hyperglycemia; diabetes mellitus 1. typu; Adult; Hypoglycemia; Kinetics; ženské pohlaví; Male; Middle Aged; Glucose; Magnetic Resonance Spectroscopy; mužské pohlaví; kinetika; Diabetes Mellitus, Type 1